Review on Fish Diversity and Habitat Relationship with Environmental Variables - Gurung, Jeevan Kumar (Damak Campus Journal, 2023)
The fish diversity and habitat are correlated with environmental variables affecting their distribution and population dynamics. The study helps to assess the status of over-exploited and endandered species. The endemic species were found to be declining due to habitat loss, degradation, alterations or modifications. Migratory fishes got disturbed by the damming in river. Upstream site had more fish assemblage than downstream. The characteristics’ of habitat like substrate, elevation, flow velocity etc. contributed to the spatial and temporal distribution of fishes.. This review aims to to expore the information related to the fish diversity and their habitat relationship to the existing environmental variables especially in river ecosystem. Majority of reviewed papers reported that fish diversity was decreased with the increase in altitude however, the result differed in terms of species richness of each taxon. The physico-chemical parameters of water played vital role in various aspects of fishes such as Juvenile stages of many fishes were found much more in well oxygenated and clear water while it was being retarded by urbanization, over-exploitation and anthropogenic activities. Fish yield was found to be increased during monsoon and summer than other seasons.